The Impact Of Solar Photovoltaic Energy On Greenhouse Gas Emissions - Lemehannet ,Aicha (University of Eloued جامعة الوادي, 2025)
The objective of this study is to investigate the influence of solar photovoltaic energy production on greenhouse gas emissions reduction in a selected group of countries from 2013 to 2022. Countries' selection was based on their geographical locations between 45°N and 45°S latitude, ensuring high solar energy potential due to year-round sunlight exposure. To reach its objective, the study employs the panel ARDL model. The model involves four variables: greenhouse gas emissions as the dependent variable, solar photovoltaic energy production, industrial added value, and electricity generation from oil, gas, and coal as independent variables. The study concludes that solar photovoltaic energy production contributes to greenhouse gas reduction in the studied countries.
The Impact of Solar Photovoltaic Energy on Greenhouse Gas Emissions: Evidence from Selected Countries Using a Panel ARDL Approach (2013-2022)
مقال
Keywords: Solar photovoltaic energy; greenhouse gas emissions; renewable energy; panel ARDL